2022
DOI: 10.4018/ijhcitp.300313
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Employee Engagement on the Effect of Inclusion and Organizational Diversity on Turnover Intention

Abstract: The purpose of this research article is to study the effect of inclusion and perceived organizational diversity on turnover intention with mediating role of employee engagement. Data of 413 participants was evaluated for this study, wherein the participants included IT Professionals working in India. PLS-SEM was used to the test the hypotheses of the study by developing a path model and carrying out measurement and structural model assessment. The results revealed that inclusion, perceived organizational diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
3
1
Order By: Relevance
“…The results for hypothesis two to the effect that diversity management programmes have a significant influence on the workplace engagement of academic staff showed that the hypothesis was rejected. This finding was inconsistent with the findings of previous scholars (Alshaabani et al, 2021;Ganji et al, 2021;Gupta & Gomathi, 2022;Jayashree et al, 2019;Kang & Sung, 2017;Mbhele & De Beer, 2021;Mistry et al, 2021;Ravikumar, 2013;Verčič & Men, 2023), who indicated that employee engagement was positively influenced by diversity management programmes. However, the diversity programmes had a significant influence on work engagement because the descriptive results revealed that the programmes were given less prominence in the university.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The results for hypothesis two to the effect that diversity management programmes have a significant influence on the workplace engagement of academic staff showed that the hypothesis was rejected. This finding was inconsistent with the findings of previous scholars (Alshaabani et al, 2021;Ganji et al, 2021;Gupta & Gomathi, 2022;Jayashree et al, 2019;Kang & Sung, 2017;Mbhele & De Beer, 2021;Mistry et al, 2021;Ravikumar, 2013;Verčič & Men, 2023), who indicated that employee engagement was positively influenced by diversity management programmes. However, the diversity programmes had a significant influence on work engagement because the descriptive results revealed that the programmes were given less prominence in the university.…”
Section: Discussioncontrasting
confidence: 97%
“…Relatedly, Ganji et al (2021) reported that diversity management training predicted employee engagement. In a study on IT professionals working in India, Gupta and Gomathi (2022) found that diversity management practices and employee engagement had a significant impact on employee engagement.…”
Section: Diversity Managementmentioning
confidence: 99%
“…However, as job fit is much more personal, supervisors play a role in this relationship. The findings of the works of Biswakarma (2015); Gubman (2004); Gupta and Gomathi (2022); Saks (2006) show conformity to the findings of this study which is employee engagement and turnover intention ordinarily have a reverse association in their relation to each other. This has been proved as hypothesis-5 is supported by the correlation value of -.261 and the p-value of .001 in the regression analysis.…”
Section: Discussionsupporting
confidence: 87%
“…Employee engagement tends to reduce the likelihood of turnover (Chebet et al, 2019;Maltseva, 2020;Oh et al, 2023). Enhanced levels of employee engagement promote a more optimistic outlook and attitude toward the workplace and reduce turnover intentions (Gupta and Gomathi, 2022;Reissov a and Papay, 2021;Saleem et al, 2021).…”
Section: Employee Engagement and Employee Turnover Intentionsmentioning
confidence: 99%